Positive policing : managing a pandemic in the world's largest democracy - Mehrotra, Sonia, (SAGE business cases., 2023)
This case details the responses of Thane Police Commissionerate in India to the challenges and uncertainties of the early 2020 COVID-19 pandemic. It documents the successful managerial strategies of police leaders who went beyond the call of duty to help the public. In particular, it explores the leadership characteristics of the Police Commissioner whose actions helped build trust and confidence among his team members and enabled them perform in a manner that brought positive perception of and trust in the police. The case encourages students to consider frameworks and concepts of organization, management, leadership, and crisis management, provoking thought about ideas and practices that can support a more humane, collaborative future for policing urban communities.